1983
DOI: 10.1590/s0004-282x1983000200010
|View full text |Cite
|
Sign up to set email alerts
|

Miopatia nemalinica: relato de um caso com estudo histoquimico e microscopia eletrônica

Abstract: Report of a case of a male child, with hypotonia since birth, along with severe feeding difficulties due to lack of swallowing, that resulted in a permanent gastrostomy. Despite the delayed motor development, he had a normal intelligence. An electromyography was suggestive of primary muscle involvement. A fresh-frozen muscle biopsy stained by the modified Gomori trichrome and processed by histochemistry and electron microscopy presented the typical nemaline rods and deficiency of type II muscle fibers. It is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Muscle biopsies were frozen in liquid nitrogen at -170 o C and cryostat sections were stained histologically, according to standard procedures 7,11 . The predominance of type I fibers with an ATPase reaction (pH 9.4, 4.6 and 4.3), moth-eaten fibers with NADHtetrazolium redutase, focal increases in acid phosphatase, and the frequency and distribution (subsarcolemmal, intermyofibrilar or mixed) of fibers with rods on MGT were determined by counting approximately 300 to 500 muscle fibers of each specimen.…”
Section: Muscle Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle biopsies were frozen in liquid nitrogen at -170 o C and cryostat sections were stained histologically, according to standard procedures 7,11 . The predominance of type I fibers with an ATPase reaction (pH 9.4, 4.6 and 4.3), moth-eaten fibers with NADHtetrazolium redutase, focal increases in acid phosphatase, and the frequency and distribution (subsarcolemmal, intermyofibrilar or mixed) of fibers with rods on MGT were determined by counting approximately 300 to 500 muscle fibers of each specimen.…”
Section: Muscle Biopsymentioning
confidence: 99%
“…Patients may also exhibit dysphagia, respiratory insufficiency, foot deformities, arch palate, scoliosis, chest deformities and superior and inferior limbs contractures [1][2][3][4][5][6][7] . Currently, NM is classified into six different forms: severe congenital, typical, intermediate congenital, juvenile, adult and other forms associated with cardiomyopathy, ophthalmoplegia and the presence of intranuclear nemaline bodies on muscle biopsy 8 .…”
mentioning
confidence: 99%
“…20 The second biopsy showed a predominance of subsarcolemmal rods and a total predominance of type I fibers (Figure 2). In patient 12, his first biopsy was done at 18 months old and the second at 14 years old.…”
Section: Immunohistochemical Analysismentioning
confidence: 98%
“…The comparative histopathologic study showed a high frequency of fibers with mixed rods (both subsarcolemmal and diffuse) and the presence of type I predominance in the first biopsy. 20 The second biopsy showed a predominance of subsarcolemmal rods and a total predominance of type I fibers (Figure 2). Patient 13 also showed a higher proportion of fibers with mixed rods in the first biopsy and a predominance of subsarcolemmal rods in the second one 10 years later (Figure 2).…”
Section: Immunohistochemical Analysismentioning
confidence: 98%